Assessing intraoperative and postoperative complications associated with tonsillectomy in children: institutional study - Sharma, Himani; Birla, Kaveri; Bareja, Srijan; Saxena, Rohit; Bhati, Pooja (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Tonsillectomy, a common procedure in children aged 2 to 18, aims to improve their well-being and minimize tonsil-related complications. Comprehensive risk assessment pre and post-surgery is crucial. This study analyzed numerous pediatric tonsillectomy cases to enhance our understanding of its safety and identify associated risk factors. Methods: A 24-month retrospective cohort study focused on 100 children (aged 2-18) who underwent unilateral or bilateral tonsillectomy at Sharda Hospital’s ENT Department. Factors like age, gender, and complications during and up to 7 days post-surgery were analyzed. Results: Gender and age were assessed for their correlation with complications in tonsillectomy patients. No significant correlation was found between gender and intraoperative or postoperative complications (p-values: 0.679584 and 0.822866). The low phi coefficient (1.501E-22) supports this, aligning with the infrequent occurrence of intraoperative complications. Age also showed no significant association with complications (p=0.77216). Postoperatively, 49.11% experienced no issues within 7 days, while common problems included pain/discomfort (31.25%), nausea/vomiting (9.82%), and secondary hemorrhage (5.36%). Conclusions: This 24-month study on 100 pediatric tonsillectomy cases revealed no significant correlation between gender/age and complications. Postoperatively, the most prevalent issues included pain/discomfort, nausea/vomiting, and secondary hemorrhage, affecting nearly half of the patients.